An Analysis of the Perception and Use of Ecodesign Practices by Companies - Mauro Maia Laruccia; Mamerto Granja Garcia (BBR: Brazilian Business Review)
This article investigates aspects related to the adoption of ecodesign practices by companies. It is descriptive in nature, based on a quantitative survey. We considered 10 indicators of ecological design principles and ecodesign practices, obtained from a review of the relevant literature, and administered a questionnaire to 340 respondents on the set of indicators investigated. We conclude that in addition to meeting legal requirements, the adoption of ecodesign practices benefits the environment and society as a whole. It also enhances firms’ social image by publicizing their concern for environmental preservation and reduces the use of materials and consumption of energy.